Comparison on the Horizontal Behaviors of Lattice-Shaped Diaphragm Wall and Pile Group under Static and Seismic Loads - Jiu-jiang Wu; Qian-gong Cheng; Hua Wen; Yan Li; Jian-lei Zhang; Ling-juan Wang (Shock and Vibration)
Lattice-shaped diaphragm wall (hereafter referring to LSDW) is a new type of bridge foundation, and the relevant investigation on its horizontal behaviors is scant. This paper is devoted to the numerical study of the comparison on the static and seismic responses of LSDW and pile group under similar material quantity in soft soil. It can be found that the horizontal bearing capacity of LSDW is considerably larger than that of pile group, and the deformation pattern of LSDW basically appears to be an overall toppling while pile group clearly shows a local bending deformation pattern during the static loading process. The acceleration response and the acceleration amplification effects of LSDW are slightly greater than that of pile group due to the existing of soil core and the difference on the ability of energy dissipation. The horizontal displacement response of pile group is close to that of LSDW at first and becomes stronger than that of LSDW due to the generation of plastic soil deformation near the pile-soil interface at last. The pile body may be broken in larger potential than LSDW especially when its horizontal displacement is notable. Compared with pile group, LSDW can be a good option for being served as a lateral bearing or an earthquake-proof foundation in soft soil.